2011
DOI: 10.1097/coc.0b013e3181dea970
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neoadjuvant Imatinib Mesylate Therapy in Sphincter-Preserving Procedures for Anorectal Gastrointestinal Stromal Tumor

Abstract: Neoadjuvant IM therapy for anorectal GIST is safe and effective. Tumor shrinkage and an extension of the distance to anal edge have a clear benefit for the local excision, in terms of feasibility, function preservation, and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Thus, we think that imatinib treatment should be given for at least 2 months or more as neoadjuvant therapy. Given the lack of evidence concerning the role of neoadjuvant and adjuvant treatments, some trials have been conducted to show the potential survival benefit or feasibility of sphincter-preserving surgery [9,10,17,[19][20][21][22]. Thus, preoperative imatinib is a reasonable option for patients with locally advanced rectal GIST occupying the pelvic space, who require multivisceral resection to achieve clear surgical margins.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, we think that imatinib treatment should be given for at least 2 months or more as neoadjuvant therapy. Given the lack of evidence concerning the role of neoadjuvant and adjuvant treatments, some trials have been conducted to show the potential survival benefit or feasibility of sphincter-preserving surgery [9,10,17,[19][20][21][22]. Thus, preoperative imatinib is a reasonable option for patients with locally advanced rectal GIST occupying the pelvic space, who require multivisceral resection to achieve clear surgical margins.…”
Section: Discussionmentioning
confidence: 98%
“…Transcoccygeal (transsacral) excision, is suitable for higher lesions (average distance from the dentate line, 5 cm) located in the posterior wall of the rectum (5,17,18). This location requires a paracoccygeal incision between the anus and coccyx, an S5 or coccygeal transection, and an incision of Waldeyer’s fascia, with exposure of the perirectal fat.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach would be the use of pre-operative IM therapy for large rectal GISTs, which may result in tumor shrinkage (20). In a previous study, neoadjuvant therapy with IM was used prior to local excision via the Kraske approach (17), which showed that preoperative IM therapy resulted in the shrinkage of GISTs and exhibited a clear benefit with regard to local excision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La potencia del imatinib en terapias de inducción de GIST del recto de alto riesgo se expresa en tasas de respuesta del 80% de los casos tratados, logrando habitualmente una respuesta parcial y una estabilización de la enfermedad, con algunos casos reportados de respuesta patológica completa 5,6 . La positiva experiencia de la neoadyuvancia con imatinib se ha multiplicado en los últimos años, determinando que actualmente sea el tratamiento estándar para los GIST de recto que requieren una cirugía radical o que está en riesgo el aparato esfinteriano [3][4][5][6][7][8][9][10] . En una experiencia de Japón, sobre 29 pacientes tratados en la era pre-imatinib por un GIST rectal, 19 fueron sometidos a una resección abdominoperineal 10 .…”
Section: Discussionunclassified